Verbal working memory in Specific Language Impairment: The effect of providing visual support - Quail, Michelle; Williams, Cori; Leitao, Suze (Informa Healthcare, 2009)
Children with Specific Language Impairment (SLI) are known to exhibit difficulties on auditory working memory (WM) tasks. This study investigated the impact of providing visual support on children's performance on an auditory WM task. Three groups of 18 children participated. The groups were children with SLI, age matched, and language matched control children. Participants completed 4 digit recall tasks using different combinations of auditory and visual input and output for a digits forwards (DF) recall condition in the first session and a digits backwards (DB) recall condition in the final session. The digit recall tasks accompany this manuscript and can be downloaded from http://www.informaworld.com/ijslp. For the DF tasks, the SLI and age matched groups recalled significantly more sequences when visual support was provided in input and output, and all groups showed a significant benefit from visual support for the DB condition. These findings provide further evidence that the provision of visual information supports working memory performance in children with SLI and typically developing children. This has implications for the support strategies currently used to assist children with WM difficulties.